Building an 'Industrial Engineering Mindset' among Indian Healthcare Executives: Toward Management of Healthcare Facilities at an Industrial Scale post the COVID-19 Pandemic. Issue 1 (June 2021) - Bhattacharyya, Som Sekhar; Chandwani, Rajesh
The COVID-19 pandemic highlighted the necessity of good quality and adequate quantity of healthcare infrastructure facilities. Healthcare facilities were provided for COVID-19 facilities with improvisation and supplementary lateral infrastructure from other sectors. However, the main point of contemplation going into the future was regarding how to quickly develop healthcare facilities. The subject domain of 'industrial engineering' (IE) and its associated perspectives could provide some key insights regarding this. The authors undertook a conceptual literature review and provided theoretical argumentation toward this. The findings provided insights regarding the application of industrial engineering concepts in healthcare facilities and services.